(untitled) (Research, Society and Development, 2021)
This work evaluated the perception of students of the Biological Sciences Course of a public university, about the Zoo of Fortaleza, Ceará. A questionnaire was applied to 29 students of the Cordados Zoo subject after a field lesson in 2017. In the analysis, female students, who knew of the zoo’s existence, had visited it before and with their families, recognized the importance of its existence and pointed out to serve for leisure and educational role. As improvements in animal welfare, the expansion and improvements in the enclosures were highlighted. The greatest learning was the experience acquired, calling more attention to the professionals, employees and administration, and less the enclosures. Most of them read the information boards and everyone was satisfied with the visit. In practice, it is clear that this environment acts as a leisure option and promotion of environmental education, reinforcing and awakening fundamental knowledge for the training of future professionals.